Penerapan Aplikasi E-TRASH pada Program Bank Sampah Mendukung Ketahanan Ekonomi Rumah Tangga - Iin Marliana (Universitas Bandar Lampung (UBL), 2023)
Application of E-TRASH in Waste Bank Program to Support Household Economic Resilience - The development of the era towards the era of society 5.0, allows every human being in his life to using modern technology such as AI and robots to meet needs and make life easier. With technology, it will be easier, because all humans are aware that getting work done quickly and easily will be better. Technological development has advantages and disadvantages, but the weakness is that it will be a concern for every human being that in Society 5.0, machines will replace all human tasks easily and which can improve the quality of human life in general. Many problems arise in life, in the form of problems in the fields of education, culture, society, economy, and other issues. One of them is the problem of garbage or waste which is increasing at this time. Seeing this situation, we innovated to create the E-TRASH application, where the application In practice, allows the process of disposing of previously useless waste, to be converted into something that has economic value, namely money/balances. This study aims to create a design for the E-TRASH application system using an Android-based operating system, this is because the use of smartphones is growing rapidly. The design of the E-TRASH application system aims to facilitate the community in minimizing the use of waste in the surrounding environment. The design of this garbage bank program system will utilize a technology called E-TRASH which will later be used for a transaction system. This design process produces a UML design which will later be used as the basis for making which includes the design containing the menus in the application. The application of E-TRASH application uses smartphone technology for customers, namely the general public, the E-TRASH mobile application implements the M-BANKING system, in this application, customers can find out the balance of transactions made, not only obtain balance information, but customers can also see the total debit and credit when transacting, this application also implements a transfer system, where customers can transfer their money to other banks if they don't want to withdraw cash.